2011
DOI: 10.1111/j.1365-3040.2011.02363.x
|View full text |Cite
|
Sign up to set email alerts
|

EIN2 regulates salt stress response and interacts with a MA3 domain‐containing protein ECIP1 in Arabidopsis

Abstract: Ethylene signalling regulates plant growth and development. However, its roles in salt stress response are less known. Here we studied functions of EIN2, a central membrane protein of ethylene signalling, and its interacting protein ECIP1 in salt stress responses. Mutation of EIN2 led to extreme salt sensitivity as revealed by phenotypic and physiological changes, and overexpression of C-terminus of EIN2 suppressed salt sensitivity in ein2-5, indicating that EIN2 is required for salt tolerance. Downstream comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 78 publications
1
90
2
1
Order By: Relevance
“…The Arabidopsis genome contains four genes encoding PDCD4 homologs, and one of them was recently reported to interact with the ethylene signaling protein EIN2; hence, it was designated ECIP1 (EIN2 C TERMINUS-INTERACTING PROTEIN1; AT4G24800). Loss-of-function mutations in ECIP1 have been shown to result in ethylene hypersensitivity (Lei et al, 2011). Apart from these findings, we lack evidence of the cellular functions of these homologs.…”
Section: Introductioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The Arabidopsis genome contains four genes encoding PDCD4 homologs, and one of them was recently reported to interact with the ethylene signaling protein EIN2; hence, it was designated ECIP1 (EIN2 C TERMINUS-INTERACTING PROTEIN1; AT4G24800). Loss-of-function mutations in ECIP1 have been shown to result in ethylene hypersensitivity (Lei et al, 2011). Apart from these findings, we lack evidence of the cellular functions of these homologs.…”
Section: Introductioncontrasting
confidence: 41%
“…RT-PCR analyses showed that mrf3-2 (ecip1-1) is a null allele, while mrf3-3 (ecip1-2) produces a truncated MRF3 mRNA (Supplemental Figures 3D and 3E;Lei et al, 2011). mrf3-1 has a T-DNA insertion in the promoter region, resulting in a slight decrease in MRF3 mRNA.…”
Section: Altered Mrf Expression Affects Flowering Time Under Long-daymentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of ethylene, the inactivation of the receptors and CTR1 results in the dephosphorylation and cleavage of the EIN2 C terminus and translocation to the nucleus, where it directly or indirectly regulates EIN3/EIL1 activation (Ju et al, 2012). An MA3 domain-containing protein (ECIP1) interacts with the EIN2 C terminus, leading to enhanced ethylene response (Lei et al, 2011). In the absence of ethylene, the EIN3/EIL1 protein levels are extremely low because of the protein turnover involving the F-box proteins Ethylene Insensitive3-Binding F-Box Protein1 (EBF1) and EBF2.…”
Section: Erfs In Ethylene Responsementioning
confidence: 99%
“…Rice has a different ethylene response phenotype in comparison with Arabidopsis and the other monocotyledonous species tested [48]. Meanwhile, unlike the positive roles of EIN2 and EIN3 in salinity response in Arabidopsis, the main positive ethylene signaling components MHZ7/OsEIN2, MHZ6/OsEIL1, and OsEIL2 all negatively regulate the salinity-tolerance of rice seedlings [48][49][50][51][52][53]. In this study, one of component of EBF1/2, EBF1 (Os06t0605900-01) was up-regulated under both drought and salt treatments compared with WT.…”
Section: The Ethylene and Jasmonate Pathways Contribute To The Improvmentioning
confidence: 99%